Association of Lunate Morphology With Progression to Scaphoid Fracture Nonunion. (May 2022) - Hein, Rachel E.; Fletcher, Amanda N.; Tillis, Rose T.; Pang, Eric Q.; Ruch, David S.; Richard, Marc J.
Background: The purpose of our study was to review a series of patients with scaphoid fractures to determine whether there was an association between lunate morphology and progression to delayed union or nonunion when treated operatively or nonoperatively. Secondary aims included evaluation of the relationship between lunate morphology and scaphoid fracture location.Methods: A retrospective review of all patients with a diagnosis of scaphoid fracture was performed at our institution between 2014 and 2017. Medical records and radiographs were evaluated to determine lunate morphology, scaphoid fracture location, treatment, and time to union. Differences between groups were determined using χ 2 analysis with significance set at P <.05. Multiple logistic regression analyses were used to evaluate scaphoid union in the setting of lunate morphology when controlling for confounders.Results: A total of 169 patients were included; 45.0% (n = 76) of patients had type I lunate morphology, and 55.0% (n = 93) had type II. In all, 64.5% (n = 49) of patients with type I lunate and 68.8% (n = 64) with type II lunate had a fracture at the scaphoid waist. Among all patients with a scaphoid fracture, type II lunates were more likely than type I lunates to progress to nonunion when treated both operatively and nonoperatively (18.3% vs 4.0%, P = .0042). Lunate facet size was not shown to be a significant risk factor for nonunion among patients with a type II lunate ( P = .4221).Conclusions: Patients with a scaphoid fracture and type II lunate morphology were more likely to progress to nonunion than patients with a type I lunate.